Werbalizacja metafory kognitywnej MYŚLENIE TO PODRÓŻ na przykładzie polskiego tłumaczenia monografii J. D. Apresjana - Węglowska, Anna Maria (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2020)
This paper is devoted to the analysis of the cognitive metaphor verbalization of THINKING IS A JOURNEY on the examples from Lexical semantics by J.D. Apresjan. Basing on the theory of cognitive metaphor by G. Lakoff and M. Johnson, the author of the article attempts to analyze and present the role of the abovementioned metaphor in scientific texts.